2019
DOI: 10.1016/j.heliyon.2019.e01865
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and determinants of complementary feeding practices in Ethiopia: A systematic review and meta-analysis

Abstract: Background & aim Concurrent estimates on the magnitude and evidence on the determinants of complementary feeding (CF) practices in Ethiopia are currently disparate. Hence, this systematic review and meta-analysis assessed the magnitude and determinants of CF among children age 6–23 months in Ethiopia. Methods Studies from various databases published until July 2018 were identified, selected, extracted and assessed for risk of bias by two authors independently. A random-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
34
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 47 publications
(56 reference statements)
10
34
1
2
Order By: Relevance
“…Additionally, one article was found by hand searching of the reference lists of the included studies. Thus, a total of 9 studies [4,[22][23][24][25][26][27][28][29] were included in the current umbrella review. The study selection and screening process is shown in Fig.…”
Section: Literature Search Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, one article was found by hand searching of the reference lists of the included studies. Thus, a total of 9 studies [4,[22][23][24][25][26][27][28][29] were included in the current umbrella review. The study selection and screening process is shown in Fig.…”
Section: Literature Search Findingsmentioning
confidence: 99%
“…Health [22][23][24][26][27][28][29] Lack of antenatal care Lack of postnatal care Place of delivery Sociodemographic [22][23][24][26][27][28][29] [26][27][28][29] Place of residence IYCF, Infant and young child feeding.…”
Section: Risk Factors Malnutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, one article was found by hand searching of the reference lists of the included studies. Thus, a total of 9 studies [4,[16][17][18][19][20][21][22][23] were included in the current umbrella review. The study selection and screening process is shown in Fig.…”
Section: Literature Search Ndingsmentioning
confidence: 99%
“…The speci c IYCF practice indicators assessed were exclusive breastfeeding, early initiation of breastfeeding, timely initiation of complementary feeding, dietary diversity, meal frequency, and minimum acceptable diet. Seven studies were done on both the magnitude and the determinants of IYCF practices [17][18][19][20][21][22][23]. The overall characteristics of the included studies, including the topic they addressed, is shown in Table 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%